Otimização estrutural para o processamento de gás natural empregando diferentes técnicas de condensação - Amaral Junior, Samuel Mathias do (2018)
Condensation mechanisms involving gas expansion or heat removal through mechanical refrigeration circuit can be combined to increase the recovery efficiency of natural gas liquid fractions (NGL). To evaluate the flexibilization strategies of flowcharts involving natural gas processing, different process arrangements simulations are performed: Turbo-Expander (TE), self-cooling (Joule-Thomson - JT) and propane refrigerant circuit (RM). Simulations are performed in Aspen Hysys © in steady state, utilizing Peng-Robinson package to predict state variables and phase envelopes. Gas compositions feeds in a range of 5.5 to 11.2% C3 + are applied. For feed mixtures with medium composition and rich in C3 + , the TERM process presents the best economic performance, while for feed mixtures with poor composition in C3 + , the TERM, TE and JTRM processes present similar profitability, except JT. Strategically, for higher LPG production, TERM should be chosen. If the main demand is dry gas (use in thermoelectric plants), the most suitable process is the JT. Following the methane, ethane, propane and butane specification limits on gas products, for all mixtures the TERM and TE processes meet the regulatory standard required by the Brazilian regulatory agency (ANP), except for JT and JTMR.